2012
DOI: 10.4049/jimmunol.1102996
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cells Induce the Generation of Novel IL-10–Dependent Regulatory Dendritic Cells by SOCS3 Activation

Abstract: Suppression of immune response by mesenchymal stem/stromal cells (MSCs) is well documented. However, their regulatory effects on immune cells, especially regulatory dendritic cells, are not fully understood. We have identified a novel Sca-1+Lin−CD117− MSC population isolated from mouse embryonic fibroblasts (MEF) that suppressed lymphocyte proliferation in vitro. Moreover, the Sca-1+Lin−CD117− MEF-MSCs induced hematopoietic stem/progenitor cells to differentiate into novel regulatory dendritic cells (DCs) (Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 51 publications
1
59
1
Order By: Relevance
“…For T reg cells the described effects are rather different. As described in various in vitro and in vivo models MSCs increased T reg levels via Gal-9 independent mechanisms such as TGF-b or PGE 2 [45,46]. Surprisingly, Gal-9 and activated MSCs restored or even decreased T reg cell counts.…”
mentioning
confidence: 75%
“…For T reg cells the described effects are rather different. As described in various in vitro and in vivo models MSCs increased T reg levels via Gal-9 independent mechanisms such as TGF-b or PGE 2 [45,46]. Surprisingly, Gal-9 and activated MSCs restored or even decreased T reg cell counts.…”
mentioning
confidence: 75%
“…Analogous to the effects of MSCs on macrophage polarization, MSCs can also promote the generation of tolerogenic DCs (Li et al 2008a;Ge et al 2009;Spaggiari et al 2009;Zhang et al 2009;Liu et al 2012b) producing anti-inflammatory cytokines and displaying enhanced phagocytic activity Liu et al 2012b) typical of tolerogenic DCs. MSC educated DCs have the capacity to suppress alloreactive responses and prolong islet allograft survival (Huang et al 2010) and to induce a state of tolerance in the context of SOT (cardiac allograft) in the presence of low dose immunosuppression (Ge et al 2009).…”
Section: Mscs In Transplantationmentioning
confidence: 99%
“…Further evidence of a contact-dependent mechanism involving activation of AKT and impaired NF-kB signaling has been proposed (Chiesa et al 2011). Finally, it has been shown that mouse embryonic fibroblast derived MSCs generate a novel population of IL-10 dependent tolerogenic DCs through an IL-10 activated SOCS3 dependent mechanism (Liu et al 2012b). MSC induction of tolerogenic DCs is a key mechanism involved in MSC modulation of immune responses; however, significant gaps in our understanding of exactly how MSCs promote the generation of tolerogenic DCs remain.…”
Section: Mscs In Transplantationmentioning
confidence: 99%
“…MSCs were prepared and purified from mouse BM cells as previously described (37,38). Mouse immature DCs (imDCs) and mature DCs (maDCs) were generated according to previously published protocols (39).…”
Section: Culture Of Mouse Bm-mscs and Bm-dcsmentioning
confidence: 99%
“…The protein expression level was analyzed by Western blot as previously described (38). Abs were obtained from Cell Signaling Technology.…”
Section: Western Blot Analysismentioning
confidence: 99%